2022
DOI: 10.1186/s13071-021-05111-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytauxzoon europaeus infections in domestic cats in Switzerland and in European wildcats in France: a tale that started more than two decades ago

Abstract: Background Cytauxzoon spp. infection is believed to be a newly emerging tick-borne disease in felids in Europe, with three species of the haemoparasite having recently been differentiated in wild felids. In Switzerland, rare infections have been documented in domestic cats in the west and northwest of the country, the first of which was in 2014. The aims of the present study were: (i) to characterize a Cytauxzoon spp. hotspot in domestic cats in central Switzerland; (ii) to elucidate the geogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…Cytauxzoon europaeus , which was identified in a wild cat in the present study, appears to be the most widespread species of its genus in Europe, reported so far in Germany, the Czech Republic, Luxembourg, Bosnia and Herzegovina, Italy, Switzerland and France [ 14 , 31 ]. While the clinical signs of infection in wild cats, if any, remain to be explored (taking into account that all studies conducted so far used postmortem sampling), domestic cats most often do not show relevant symptoms (e.g.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Cytauxzoon europaeus , which was identified in a wild cat in the present study, appears to be the most widespread species of its genus in Europe, reported so far in Germany, the Czech Republic, Luxembourg, Bosnia and Herzegovina, Italy, Switzerland and France [ 14 , 31 ]. While the clinical signs of infection in wild cats, if any, remain to be explored (taking into account that all studies conducted so far used postmortem sampling), domestic cats most often do not show relevant symptoms (e.g.…”
Section: Discussionmentioning
confidence: 78%
“…While the clinical signs of infection in wild cats, if any, remain to be explored (taking into account that all studies conducted so far used postmortem sampling), domestic cats most often do not show relevant symptoms (e.g. anemia) and remain clinically unaffected [ 31 ]. This is in contrast to what is known of C. felis in North America [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cats, infections with another apicomplexan tick-borne hemoprotozoan, Cytauxzoon spp., emerged, with a report in 2018 of five domestic kittens from the northwest and west of Switzerland presenting with severe anemia [ 262 ]. Furthermore, six infected domestic cats were identified in 2019 in the central part of Switzerland, triggering a nationwide epidemiological study, in which one seropositive (1 of 881 randomly selected cats), and one PCR-positive cat (1 of 501 anemic cats), both originating from the region of the Jura mountains, were identified [ 263 ]. In summary, these cases in companion animals indicate a higher risk of hemoprotozoan infections in the western part of Switzerland, where also tick vectors such as D. reticulatus can frequently be encountered [ 25 ].…”
Section: Central Europementioning
confidence: 99%
“…However, increasing the intensity of the studies of this pathogen after the first finding in Europe may lend this explanation more credence. The last findings of the pathogen in the samples of European wildcats collected at the end of the 20th century confirm the presence of this parasite in France during that period [ 65 ]. Cytauxzoon spp.…”
Section: Discussionmentioning
confidence: 72%